(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Pharmacological efficacy of Caulerpa racemosa (Chlorophyta) sulfated polysaccharidic (SPs) fractions (F Iâ†’III) on models of coagulation and inflammation has been demonstrated, but not their effects on thrombin generation (TG). This study examined fractions for composition and physical-chemical characteristics and in vitro inactivation of TG by F I and F II in 60-fold diluted human plasma using continuous method. Papain-extraction yield of 0.7% revealed F Iâ†’III by DEAE-cellulose chromatography, with differences among the relative proportions of sulfate (17.37-24.00%), total sugars (30.03-48.34%) and absence of proteins. Charge density patterns and molecular sizes > 100 kDa of the fractions were verified by both agarose/polyacrylamide analyses, respectively. These electrophoreses combined with toluidine blue/Stains-All also indicated nonSPs. Anticoagulant effects of 4.76 (F I), 12.00 (F II) and 2.32 (F II) IU mg-1 by activated partial thromboplastin time test were recorded against heparin (193 IU mg-1), without changes in prothrombin time. Diluted plasma treated with F I and F II reduced concentration-dependent and sulfation pattern TG by both intrinsic and extrinsic pathways, with 50% inactivation by intrinsic pathway of F II even at 4.1 µg. Heparin abolished TG at least 4-fold lower. Therefore, C. racemosa produces SPs with TG inhibition.